The Problem of Timely Diagnosis of Multiple Primary Colon Cancer - N. V. Nudnov; S. V. Goncharov; U. S. Stanoevich; O. P. Bliznyukov; D. S. Kontorovich (Вестник рентгенологии и радиологии)
Multiple primary colon cancer is an urgent medical problem of our time, which is associated with a steady increment in the incidence of the above disease and with the high complexity of its diagnosis. According to the literary sources, the incidence of this form of cancer of the colon has recently amounted to as much as 17% among all multiple primary neoplasms and this organ is a very common site. The paper describes a clinical case confirming the need for a thorough diagnosis of multiple primary colon cancer, by applying radiation techniques to further define treatment policies.